Impact of sleep and screen times on incidence of overweight in European children and adolescents. (13th November 2019) - Guzman, V; Arvidsson, L; Lissner, L; Hunsberger, M
Abstract: Background: A deeper understanding of the modifiable risk factors leading to excess weight in children and adolescents can provide unique opportunities for preventing the immediate and long-lasting health consequences of overweight. The aim of the study was to explore independent, prospective associations of screen time and sleep duration with incident overweight in a sample of European children. Methods: Data from 4285 participants of the IDEFICS/I.Family cohort who were followed-up from 2009/2010 to 2013/2014 was analyzed. Hours per day of screen time and sleep duration were collected by parental report at baseline. Logistic regression analyses were carried in separate and mutually adjusted models controlled for sex, age, European country region, parental level of education and baseline BMI z-scores. Results: At baseline screen time (hours/day) and sleep duration (hours/day) were inversely correlated behaviors (rs= -0.226, p<.001), indicating the necessity of exploring their separate and joint effects on the weight trajectory. In the non-overweight/non-obese population at baseline (N = 3734), separate models suggest that every hour increase on screen time and every hour decrease on sleep duration were associated with higher odds of the child becoming overweight or obese at follow up (OR = 1.156, 95% CI 1.015-1.316 and OR = 1.226, 95% CI 1.053- 1.428 respectively). In the mutually adjusted model, the screen time association was attenuated to non-significance (OR = 1.125, 95% CI 0.986- 1.284), while the association with sleep duration was also attenuated but remained statistically significant (OR = 1.198, 95% CI 1.026-1.398). Conclusions: Both screen time and sleep duration are significant predictors of incident overweight in children and adolescents. However, according to our results sleep duration plays a stronger role than screen time, suggesting an increased value of overweight prevention strategies that emphasize adequate sleep duration. Key messages: A holistic and integrated approach is needed to prevent overweight from early age and with a life-course perspective. New strategies for overweight prevention could benefit from prioritizing interventions that promote adequate sleep duration and reduce excessive screen time.